PENERAPAN MODEL KOOPRATIF TIPE EXAMPLE NON EXAMPLE UNTUK MENINGKATKAN HASIL BELAJAR IPA KELAS IB SD NEGERI 144 PEKANBARU - Elna Hajjiyah; Zulkifl '; Hamizi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: this background of research is the law result of the value of Science course from the student’s average value 59, 05 of 21 students while the Minimum Criteria of Mastery (MCM) is 70. This research is Classroom Action Research (CAR). The purpose of this research is to increase the quality of learning progress and the result of science learning of the students from 1st B class of State elementary school 144 Pekanbaru using cooperative learning model which type is example non example into learning progress. This research conducted on March of the school years 2014/2015 in State elementary school 144 Pekanbaru at 1st B Class. The instruments of the research are teacher and student’s activities note and the test of the learning. The technique of data analysis in this research is descriptive. This research presenting an increasing of the teacher’s activity at the first meeting 67% with good category, the II cycle at second meeting 75% with good category, II cycle at first meeting 92% with the category very good, the II cycle at the second meeting 96%. At the same time, the student’s activity at the I cycle of first meeting 67% with good category, the I cycle at the second meeting 75% with good category, II cycle at the first meeting 92% with the very good category and the II cycle at the second meeting 96%. Based on the student’s result learning the increasing of the value can be noticed from 59, 05 to 71, 67 at I cycle with the presentence of increasing 21, 37% from the basic value. In II cycle the average value 86, 90 with presentence of the value 47, 16% the increasing of the result’s learning science is noticed from the mastery of learning which is reach the Minimum Criteria of Mastery (MCM) 70 in each daily examinations. The result of this research shows that the application of cooperative learning model which type is example non example in learning science can increase the learning result.Keyword : Cooperative Model Type Example Non Example, Science Learnig Result.